1980
DOI: 10.1042/bj1920033
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes during reticulocyte maturation in culture. A comparison of genetically different sheep erythrocytes

Abstract: A simple culture technique was used to follow sheep reticulocyte maturation. Cells remained in good condition without lysis for at least 7 days and maintained normal intracellular ATP concentrations. Amino acid and nucleoside transport were measured during maturation together with changes in reduced glutathione (GSH), amino acid, K+ and Na+ concentrations. Reticulocytes of the genetic types high-K+ and low-K+, high-GSH and low-GSH; nucleoside-permeable and nucleoside-impermeable were indistinguishable both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…However, the loss of transport and inhibitor binding activity was faster than the apparent reticulocyte maturation rate as judged by the loss of reticulin, suggesting that different biochemical parameters have different regression schedules (see also Tucker & Young, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the loss of transport and inhibitor binding activity was faster than the apparent reticulocyte maturation rate as judged by the loss of reticulin, suggesting that different biochemical parameters have different regression schedules (see also Tucker & Young, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Sources of other reagents used in the present study are detailed elsewhere (Tucker & Young, 1980;Jarvis et al 1982). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, erythrocyte amino-acid transport has been shown to be important for the provision of amino-acid precursors for intracellular glutathione biosynthesis [15,17,20,33,39,40,48,57,60,61]. Erythrocyte amino-acid transporters also function as efflux routes for amino acids produced by protein degradation during reticulocyte maturation and perhaps also by hydrolysis of small peptides entering the cell from the plasma [18,[34][35][36]47]. Amino-acid transport across the erythrocyte plasma membrane is required for the development of the intracellular stages of mammalian and avian malarial parasites [27,44], and there is some evidence that erythrocytes may participate in interorgan transport of amino acids [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the erythrocyte band 3 anion-exchange transporter has a significant affinity for glycine and some other amino acids Ellory et al 1981 b). Physiologically, erythrocyte amino acid transporters provide the amino acid precursors (L-cysteine, L-glutamate, glycine) for intracellular glutathione (GSH) biosynthesis (Young et al 1975(Young et al ,1976Young, Tucker & Kilgour, 1982; Maede, Inaba & Taniguchi, 1983;Inaba & Maede, 1984) and may also participate in the efflux of amino acids produced by protein degradation during reticulocyte maturation (Tucker & Young, 1980). It has also been suggested that amino acid transporters are responsible for the efflux of intracellular amino acids arising from erythrocyte hydrolysis of plasma peptides (King, York, Chapman & Kuchel, 1983;King & Kuchel, 1984Vandenberg, King & Kuchel, 1985).…”
Section: Introductionmentioning
confidence: 99%